Intraoperative recurrent laryngeal nerve monitoring in unconventional thyroid surgery. Issue 7 (25th July 2022) - Filippo, Carta; Valeria, Marrosu; Valeria, Pinto; Melania, Tatti; Bontempi, Mauro; Cinzia, Mariani; Roberto, Puxeddu
Abstract: The most common surgical risk after total thyroidectomy remains the recurrent laryngeal nerve (RLN) injury. Nowadays, the use of intraoperative nerve monitoring systems (IONM) such as the endotracheal tube‐based is recommended to prevent RLN palsy. The use of the nerve monitoring is standardized by dedicated guidelines on the basis of a normal laryngeal anatomy, but previous head and neck surgical procedures may complicate its application. The authors herewith present a case of a non‐conventional use of endotracheal tube‐based IONM in a 72‐year‐old patient who underwent to a second‐stage total thyroidectomy for metastatic papillary cancer incidentally detected after an open partial horizontal laryngectomy (OPHL) extended to one arytenoid (Type IIa + ary left) for squamous cell carcinoma. The use of the endotracheal tube‐based IONM in such particular case where the function of the only remaining arytenoid had to be absolutely preserved was effective in avoiding the RLN accidental injury. The authors reviewed the non‐traditional use of IONM and described the procedure in case of thyroidectomy in patients previously treated by OPHL. Abstract : Intraoperative Neuro‐monitoring can offer a paramount surgical benefit in case of unconventional surgical scenarios such as OPHL. It can represent a safe and reliable indicator for the recurrent laryngeal nerve identification when facing with major anatomical changes hazarding laryngeal function.